Kompetensi Penyuluh Pertanian dalam Pelaksanaan Kegiatan Penyuluhan di Kecamatan Harau, Kabupaten Lima Puluh Kota - Kurniasih, Dedeh Kurniasih (Fakultas Pertanian, Universitas Lampung, 2022)
Extenesion Workers competence is their ability instructor in carrying out their duties. The duties of BPP Harau's agricultural Extenesion Workers consist of three components, namely setting programme planning, carrying out extension, and conducting extension evaluations. This study aims to identify the competency level of Extenesion Workers in carrying out extension in the ​​Harau District working are. This research was conducted from March to May 2020 with 13 Extenesion Workers in the Harau District working area as respondents. This study uses a descriptive statistical analysis using Likert scales 1-3. The results showed that the competence of Extenesion Workers in making extension mateials had an average scoreof 2,5 and was classified as competent, competence in making and using conventional extension media had an average score of 2,3 and was classified as competent enough, competence in making and using extension media based on information technology had an average a score of 1,4 and classified as incompetent, and competence in interacting with groups hadan average score 2.4 and classified as competent. Overall the competency of the Extenesion Workers in carrying out exntension in the Harau District working area had an average score 2.1 and classified as competent.